Dampak Working Capital Turn Over dan Debt to Equity Ratio Pada Return on Invesment di PT Ultra Jaya Milk Industry & Trading Company Tbk - Nadyya Awaliyyah; Vemy Suci Asih; Mila Badriyah (Indonesian Journal of Economics and Management, 2021)
One way to measure the level of success of the company is to look at the amount of profit earned. This study aims to determine the effect of Working Capital Turn Over and Debt to Equity Ratio on Return On Investment either partially or simultaneously at PT. Ultra Jaya Milk Industry & Trading Company, Tbk. period 2005- 2020. The research method used is descriptive verification with a quantitative approach, and the data used are secondary data obtained from the annual reports of PT. Ultra Jaya Milk Industry & Trading Company, Tbk. 2005-2020. The results show that there is a significant effect between Working Capital Turn Over and Debt to Equity Ratio simultaneously on Return On Investment of 45%. Partially, Working Capital Turn Over has a significant negative effect on Return On Investment of 31.2% and partially Debt to Equity Ratio has a significant negative effect on Return On Investment of 24.8%. This shows that the existence of Working Capital Turn Over and Debt to Equity Ratio can affect the company's rate of return on investment.